USING FREE ONLINE FORM TO ENHANCING THE STUDENT ADMISSION IN ISLAMIC BOARDING SCHOOL - Luluk Indarti (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2021)
This study explores new media for the admission system at Darul Falah Islamic Boarding School, Tulungagung. Innovations in registering new students need to be carried out to respond to the COVID-19 pandemic. Islamic boarding schools require a registration form that can be accessed online to accept new students. This study uses a qualitative method. The data was collected through interviews, observation, and documentation. The waterfall analysis model is used for analyzing the admission system. The interactive analysis model is used for the data analysis technique. The validity of the data is done by triangulation of techniques and sources. The study results: The service for accepting new students during the covid 19 pandemic was carried out online using the google form media. The use of the media is effortless, so it is easy to apply. However, parents of prospective students need a long time to use the online form. This research implies that the free online form provided by Google can be a practical and easy solution for Islamic boarding schools that have limited resources in accepting new students during the COVID-19 pandemic.